MOŻLIWOŚCI REALIZACJI USŁUG UŻYTECZNOŚCI PUBLICZNEJ W PROCESIE WDRAŻANIA KONKURENCJI W SEKTORACH INFRASTRUKTURALNYCH - Bobińska, Krystyna (Wydział Prawa i Administracji UAM, 2000)
A univocal determination of the function of public services and of their addressee is one of necessary conditions of implementation of the market mechanism in the sectors of economic infrastructure the status of which is of public nature. Within hitherto existing solutions the public powers were not obliged to determine these functions in a precise manner because they have been themselves owners of the enterprises which were compelled to assume the functions in question under a form of some generally formulated tasks. After having given short definitions of several fundamental notions the Author characterises the specificity of monopoly in infra-structural sectors of public order, next - internal sources of financing these services within the framework of the State monopoly and, finally, problems of identification and operationalisation of the tasks of public nature of usefulness. When discussing all these questions the Author has recourse to a series of examples spooned out of highly developed countries.
REALISATION POSSIBILITIES REGARDING PUBLIC SERVICES WITHIN THE PROCESS OF COMPETITION IMPLEMENTATION IN INFRASTRUCTURAL SECTORS